Hubungan Pola Makan Terhadap Kejadian Anemia Pada Ibu Hamil di PKMS Curugbitung Tahun 2024 - Jamilah Jamilah; Kusniati Kusniati (Universitas Pahlawan Tuanku Tambusai, 2025)
Anemic conditions during pregnancy are common and can put both mother and baby at risk if not managed properly. One of the leading causes is malnutrition. This research aims to analyze the relationship between maternal nutritional status and the occurrence of anemia in pregnant women who visited Curug Bitung Community Health Center, Lebak Regency in 2024. This research uses convenience sampling method. Information is collected through questionnaires and analyzed using Chi-square test. The results of the study show that out of 85 respondents, 59 people (69.4%) were diagnosed with anemia, while 60 pregnant women (70.6%) faced malnutrition. Statistical analysis shows a significant relationship between maternal age, income and nutritional status with the incidence of anemia (p value <0.05). However, no significant association was found between gestational age and number of pregnancies with the prevalence of anemia (p 0.05). Based on the results of this study, malnutrition is a contributing factor to anemia among pregnant women in Curug Bitung Community Health Center. Therefore, education on healthy eating and nutritional recovery is very important to reduce the risk of anemia during pregnancy.